THE USE OF INFORMATION TECHNOLOGY IN TEACHING ENGLISH (Лучшие интеллектуальные исследования, 2025)
Abstract: the use of Information Technology in teaching English is important today in making the educational process more efficient and interactive. Information technology, including the internet, mobile applications, multimedia tools and various platforms, offers new opportunities to teachers and students. In this article, we will reflect in detail on the advantages of Information Technology in teaching English, their application and its impact on the educational process.